2020
DOI: 10.1186/s13019-020-01281-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of right ventricle pulmonary artery coupling on right ventricular function in post operative tetralogy of Fallot patients underwent for pulmonary valve replacement

Abstract: Background To evaluate RV-PA coupling in post operative TOF patients with ventricular dilatation underwent for PVR and investigate the correlation between ventricular functions measuring Ea/Emax ratio using cardio magnetic resonance and the effect of surgical type at primary repair of TOF on coupling. Method RV-PA coupling was measured noninvasively by Ea/Emax ratio from CMRI and ECHO. From CMRI results the patients were divided in two groups, RV-PA coupling and RV-PA uncoupling. Ea/Emax ≤1 was considered fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…found that long‐term follow‐up TAPSE/PASP assessment of RV–PA coupling was simple, applicable, and significant to prognosis, suggesting that RV–PA uncoupling is common amongst these patients 114 . Their results aligned with those of previous studies that analysed RV–PA coupling in similar individuals but employed Ees/Ea 115,116 . TAPSE/PASP detects subclinical RV dysfunction in patients after TOF repair, consequently preventing poor cardiovascular outcomes 117 .…”
Section: Tricuspid Annular Plane Systolic Excursion/pulmonary Artery ...supporting
confidence: 77%
See 1 more Smart Citation
“…found that long‐term follow‐up TAPSE/PASP assessment of RV–PA coupling was simple, applicable, and significant to prognosis, suggesting that RV–PA uncoupling is common amongst these patients 114 . Their results aligned with those of previous studies that analysed RV–PA coupling in similar individuals but employed Ees/Ea 115,116 . TAPSE/PASP detects subclinical RV dysfunction in patients after TOF repair, consequently preventing poor cardiovascular outcomes 117 .…”
Section: Tricuspid Annular Plane Systolic Excursion/pulmonary Artery ...supporting
confidence: 77%
“…114 Their results aligned with those of previous studies that analysed RV-PA coupling in similar individuals but employed Ees/Ea. 115,116 TAPSE/PASP detects subclinical RV dysfunction in patients after TOF repair, consequently preventing poor cardiovascular outcomes. 117 Egbe et al 118 measured TAPSE/PASP in 84 patients with persistent pulmonary regurgitation post-operatively with repaired TOF.…”
Section: Tricuspid Annular Plane Systolic Excursion/pulmonary Artery ...mentioning
confidence: 99%
“…[52][53][54] The difference in RV response to these two types of volume overload may be explained by abnormal right ventricular-pulmonary arterial (RV-PA) coupling in pulmonary regurgitation. 55,56 RV can increase its contractility up to five times of baseline value in PH. After that, the RV dilates to limit the decrease in the stroke volume.…”
Section: Comparison Of Qualitative Assessment Of Tricuspid Annular Pl...mentioning
confidence: 93%
“…Of note, these different studies use different methods, so direct comparison is impossible. A recent study has published on ventriculo-arterial coupling in rTOF, non-invasively assessed by using cardiac magnetic resonance (CMR) derived RV volumes only ( 40 ). The need for pressures in the equation is supposedly eliminated by forcing the linear regression of the end-systolic pressure volume relation through the origin.…”
Section: The Phenotype Of Right Ventricular Dysfunctionmentioning
confidence: 99%